Arsitektur Healing Environment untuk Rumah Sakit Perawatan Pasien Covid-19 di Makassar - Mustafa, Fajari; Marwati, Marwati; Amin, Burhanuddin (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2024)
Abstract_Health is a crucial aspect of urban development and human resource advancement. According to Indonesia's Health Law No. 9 of 1960 and the 1975 WHO definition, health encompasses physical, mental, and social well-being. The city of Makassar faces significant challenges in providing healthcare services, particularly with the growing demand for hospital referrals. The Covid-19 pandemic, caused by the Coronavirus, was first identified in Wuhan, China, in December 2019 and rapidly spread worldwide, including to Indonesia. This pandemic necessitated mitigation measures, including social restrictions as outlined in Government Regulation No. 21 of 2020. This study aims to design a specialized hospital for Covid-19 patients in Makassar, applying a healing environment architectural approach. The research methodology includes site analysis, primary and secondary data collection, and synthesis of concepts based on design elements that support patient recovery. The results show a hospital design incorporating natural lighting, optimal ventilation, and integration of natural elements, which enhance patients' physical and psychological comfort and accelerate the healing process.